as , anbia - KIND TO ANIMALS (Lahore, 2022)
Through engaging illustrations and simple language, this book teaches valuable lessons on how to treat animals with care and respect. Ideal for children aged 2 to 6, it$1 (Bs a fun and educational way to instill good behavior.s
Keywords: illustrations and language